An Examination of the Impact of Medical Malpractice Litigation on the Performance of Health Workers in Uganda. - Paul Richard Kabanda (Uganda Christian University, 2024)
Medical malpractice litigation is a growing trend in most developing countries and many countries are seeking ways to cope with the problem. Practicing safe behavior regarding patients is an essential part of a health worker’s ethical and professional standards. Despite this, health workers practice behaviors that run counter to patient safety, including practicing defensive medicine, hesitating to disclose incidents of malpractice to patients and failing to report these incidents of malpractice to the hospital administrations. Health worker’s risk of malpractice litigation seems to be a relevant factor affecting these behaviors. The objective of this study was to examine the impact of medical malpractice litigation on the performance of health workers. The study sought discuss the legal framework surrounding medical malpractice in Uganda, analyzed the state of medical malpractice litigation in Uganda, and analyzed the adequacy of the existing legal frameworks in addressing the medical malpractice. It has been established that there is a need for a common definition of medical malpractice, a common legislation that will save the situation of referring to multiple laws when adjudicating on medical negligence suits. The health workers have suffered from psychological distress when facing medical litigation. Such distress has led to underperformance of health workers. The costs associated with medical malpractice and the ensuing litigation have been considerable and trigger different responses from the health worker. The environment is characterized with several factors combined to create worker resentment and unhappiness about their professions and the regulatory systems within which they operate.